2022
DOI: 10.1097/ico.0000000000003052
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of a New Noninvasive Automatic Ocular Surface Analyzer for the Diagnosis of Dry Eye Disease—Two-Gate Design Using Healthy Controls

Abstract: The purpose of this study was to assess the diagnostic performance of measurements from a new noninvasive, automated ocular surface analyzer (IDRA) in the diagnosis of dry eye disease (DED). Methods:We prospectively identified patients with and without DED using best practice methods. Subsequently, all participants underwent IDRA analysis, consisting of 5 components: noninvasive tear film break-up time, tear meniscus height, lipid layer interferometry, eye blink quality, and infrared meibography. The manufactu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Another study found that a new, non-invasive ocular surface analyzer (IDRA) effectively identifies dry eye disease (DED) and shows good agreement with existing diagnostic methods. This suggests that IDRA could be a valuable tool for initial DED screening and guiding treatment decisions in outpatient settings [17].…”
Section: Discussionmentioning
confidence: 99%
“…Another study found that a new, non-invasive ocular surface analyzer (IDRA) effectively identifies dry eye disease (DED) and shows good agreement with existing diagnostic methods. This suggests that IDRA could be a valuable tool for initial DED screening and guiding treatment decisions in outpatient settings [17].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical assessment items were measured at the time of the DQS-LX switchover. Symptoms were assessed using the Standard Patient Evaluation of Eye Dryness (SPEED) validated questionnaire (scale, 0–28) [17,18]. Tear meniscus height (TMH) was quantitatively measured using an IDRA (SBM Sistemi, Torino, Italy) [17, 18].…”
Section: Methodsmentioning
confidence: 99%
“…Symptoms were assessed using the Standard Patient Evaluation of Eye Dryness (SPEED) validated questionnaire (scale, 0–28) [17,18]. Tear meniscus height (TMH) was quantitatively measured using an IDRA (SBM Sistemi, Torino, Italy) [17, 18]. Lid margin abnormalities (plugging of the meibomian gland orifices and vascularity of lid margins) [19], FBUT, corneal and conjunctival fluorescein staining (CFS) [20], and meibum grade (0-3) [21] were evaluated using slit-lamp microscopy.…”
Section: Methodsmentioning
confidence: 99%
“…A prospective study with 75 patients (40 with DED and 35 healthy subjects) found good concordance between the IDRA ocular surface analyzer and standard diagnostic procedures in differentiating between individuals with normal ocular function and those with dry eye disease. It had an area under the curve of 0.868 (95% confidence interval: 0.809-0.927) to detect DED [13].…”
Section: Methodsmentioning
confidence: 99%